Nuclear magnetic resonance lipoproteins are associated with carotid atherosclerosis in type 1 diabetes and pre‐eclampsia. Issue 1 (2nd July 2020) - Amor, Antonio J.; Vinagre, Irene; Valverde, Maite; Urquizu, Xavier; Meler, Eva; López, Eva; Quirós, Carmen; Giménez, Marga; Codina, Laura; Conget, Ignacio; Barahona, Maria J.; Perea, Verónica
Abstract: Aims: Persistence of lipoprotein abnormalities in type 1 diabetes (T1D) and/or pre‐eclampsia could be associated with cardiovascular disease (CVD). We assessed differences in the advanced lipoprotein profiles according to the presence of both conditions and their differential association with atherosclerosis. Material and methods: We recruited 112 women without CVD and last pregnancy ≥5 years previously, divided into four groups (n = 28 per group): (a) T1D and previous pre‐eclampsia; (b) T1D without pre‐eclampsia; (c) pre‐eclampsia without T1D; and (d) controls (without T1D/pre‐eclampsia). Groups were matched by several risk factors, and diabetes duration and retinopathy in T1D. Carotid intima‐media thickness (IMT) and the presence of plaque (IMT ≥1.5 mm) were assessed by ultrasonography. The lipoprotein profile was evaluated by nuclear magnetic resonance (NMR) spectroscopy. Results: The participants were 44.9 ± 7.8 years old. Carotid plaque presence was 20.5%, with a higher prevalence in T1D and/or pre‐eclampsia vs controls ( P < .05). High‐density lipoprotein (HDL)‐related variables differed among groups, mainly driven by an increase in T1D ( P < .05), whereas triglyceride‐related variables were increased in pre‐eclampsia [medium very low‐density lipoprotein (VLDL) particles and triglyceride enrichment in HDL and low‐density lipoprotein (LDL)]. Overall, in multivariate‐adjusted models, LDL‐related variables were the most strongly associated with atherosclerosis ( P < .05). In age‐ and statin‐adjusted models, previous pre‐eclampsia showed an independent association with triglyceride‐related variables (plaque: medium‐VLDL‐particles, OR 1.550 [1.013‐2.374]; HDL‐cholesterol/HDL‐triglycerides ratio, OR 0.411 [0.175‐0.967]). Regarding T1D, HDL‐parameters were also differentially associated (maximum‐IMT: HDL‐cholesterol/HDL‐particles ratio, β = −.258, P = .036). Conclusions: NMR lipoproteins were differentially and independently associated with atherosclerosis in T1D/pre‐eclampsia. Further studies are needed to ascertain the role of NMR parameters as CVD biomarkers in this high‐risk population.